Dolled up for murder [large type] - Cleland, Jane K. (Cleland, Jane K. Josie Prescott antiques mysteries., 2012)
Showing a recently acquired doll collection to an investor who is subsequently shot and killed, antiques dealer Josie Prescott is horrified when one of her employees is kidnapped by an abductor who demands the doll collection as ransom.